Uptake of Home-Based Syphilis and Human Immunodeficiency Virus Testing Among Male Partners of Pregnant Women in Western Kenya. Issue 9 (September 2017) - Mark, Jennifer; Kinuthia, John; Roxby, Alison C.; Krakowiak, Daisy; Osoti, Alfred; Richardson, Barbra A.; Gone, Molly Ann; Asila, Victor; Parikh, Saloni; Farquhar, Carey
Abstract : Background: Few men are tested for syphilis or human immunodeficiency virus (HIV) during their partner's pregnancy, a high-risk period for HIV and syphilis transmission. Offering home-based rapid testing of syphilis to couples during pregnancy can support prevention efforts to reduce transmission of sexually transmitted diseases and adverse pregnancy outcomes. Methods: We assessed men's uptake of paired (separate tests, single blood draw) point-of-care syphilis and HIV tests within a randomized controlled trial of pregnant women who received clinic or home partner HIV testing. We evaluated acceptance of paired HIV-syphilis testing during pregnancy or at 6 months postpartum, and evaluated whether addition of syphilis testing affected the uptake of HIV testing among men. Results: Of 601 women, we were unable to meet 101 male partners, and 180 tested before syphilis tests were available. Paired syphilis and HIV testing was offered at home to 80 men during pregnancy and to 230 men postpartum. For syphilis, 93% of men agreed to test during pregnancy and 98% agreed postpartum. For paired syphilis and HIV testing, 91% of men tested for both during pregnancy and 96% tested postpartum. Before syphilis test introduction, 96% of men accepted HIV testing, compared with 95% of men who accepted HIV testing when paired testing was offered. Conclusions: Uptake of syphilis and HIV testing was high among male partners offered couple testing at home. Introducing syphilis testing did not adversely affect HIV testing among men. Point-of-care diagnostics outside facilities can increase testing of male partners who rarely accompany women to antenatal clinics. Abstract : A study in Nyanza Province, Kenya, found that point-of-care syphilis testing is as acceptable to male partners of pregnant women as human immunodeficiency virus testing and does not adversely affect human immunodeficiency virus testing.